Identification of the Corticobulbar Tracts of the Tongue and Face Using Deterministic and Probabilistic DTI Fiber Tracking in Patients with Brain Tumor - Jenabi, M.; Peck, K.K.; Young, R.J.; Brennan, N.; Holodny, A.I. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The corticobulbar tract of the face and tongue, a critical white matter tract connecting the primary motor cortex and the pons, is rarely detected by deterministic DTI fiber tractography. Detection becomes even more difficult in the presence of a tumor. The purpose of this study was to compare identification of the corticobulbar tract by using deterministic and probabilistic tractography in patients with brain tumor.MATERIALS AND METHODS: Fifty patients with brain tumor who underwent DTI were studied. Deterministic tractography was performed by using the fiber assignment by continuous tractography algorithm. Probabilistic tractography was performed by using a Monte Carlo simulation method. ROIs were drawn of the face and tongue motor homunculi and the pons in both hemispheres.RESULTS: In all subjects, fiber assignment by continuous tractography was ineffectual in visualizing the entire course of the corticobulbar tract between the face and tongue motor cortices and the pons on either side. However, probabilistic tractography successfully visualized the corticobulbar tract from the face and tongue motor cortices in all patients on both sides. No significant difference (P < .08) was found between both sides in terms of the number of voxels or degree of connectivity. The fractional anisotropy of both the face and tongue was significantly lower on the tumor side (P < .03). When stratified by tumor type, primary-versus-metastatic tumors, no differences were observed between tracts in terms of the fractional anisotropy and connectivity values (P > .5).CONCLUSIONS: Probabilistic tractography successfully reconstructs the face- and tongue-associated corticobulbar tracts from the lateral primary motor cortex to the pons in both hemispheres.CBTcorticobulbar tractFAfractional anisotropyFACTfiber assignment by continuous tractography